Possibilities of the pathogenic therapy in the treatment of acute intestinal infections in early age children - I. V. Kuimova; E. I. Krasnova; A. V. Vasyunin; V. V. Varennicova; N. A. Barabanova (Лечащий Врач)
There is the analysis of the pathogenic therapy of the acute enteric infections in children of early age. The use of gelatin tannat in the treatment of the toxic syndrome and diarrhea in children with gastroenteric infections was very effective.